Observation of human-animal interaction for research (OHAIRE) behavior coding in a randomized control trial of children with attention-deficit hyperactivity disorder (ADHD) and a canine-assisted intervention - Nieforth, Leanne O.; Guerin, Noémie A.; Stehli, Annamarie; Schuck, Sabrina E. B.; Yi, Katherine; O’Haire, Marguerite E. (Frontiers in Psychiatry, 2024)
Introduction Diagnosed in about 10% of children in the United States, attention-deficit hyperactivity disorder (ADHD) is characterized by symptoms including inattention, hyperactivity, and impulsivity. Traditional interventions, such as pharmacological and psychological interventions, are often used in conjunction with integrative health options, such as animal-assisted interventions. The objective of this manuscript is to report behavior coding findings from a randomized control trial of children with ADHD. Methods As part of a larger randomized control trial focused on the efficacy of combining a canine-assisted intervention (live therapy dog or control stuffed dog) with cognitive behavioral therapy for children with ADHD, the current manuscript focuses on video-captured behavior observations (n = 35 children, approximately 322 minutes of data). Data were extracted and coded using the Observation of Human-Animal Interaction Research (OHAIRE) Coding System. Behavior codes are reported as summary scores for the following domains: animal social interaction and human social interaction (further separated into human-adult social interaction and human-peer social interaction). Repeated measures mixed models analyses were performed using SAS PROC GLIMMIX to evaluate group differences and change across the study period. Results There were no significant differences in how much children interacted with the live therapy dogs versus control stuffed dogs. With respect to human-to-human social interactions, children showed greater increases over time in human-directed social interactions in the presence of live therapy dogs compared to stuffed dogs (p = .020). Over the course of the 12-week intervention, children increased in interactions with both adults (p = .006) and their peers (p = .014); however, there were more increases over time in adult-directed social interactions in the live animal condition compared to the control stuffed animal condition (p < 0.0001). Discussion & conclusions Findings suggest changes in social interaction when participating in this canine-assisted intervention, specifically greater increases in human-to-human social interactions over time when a live therapy dog is present compared to a control stuffed dog. Children appear to engage relatively equally with both live and stuffed dogs; however, the impact of animals on human socialization differs based on if a live animal is present. Future studies should consider incorporating behavior coding analysis into studies of canine-assisted interventions to identify how human-animal interactions may be moderators or mechanisms for psychosocial outcomes.